2009
DOI: 10.1016/j.atmosenv.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in traffic-related particulate matter at New York City high schools

Abstract: Relatively little is known about exposures to traffic-related particulate matter at schools located in dense urban areas. The purpose of this study was to examine the influences of diesel traffic proximity and intensity on ambient concentrations of fine particulate matter (PM 2.5 ) and black carbon (BC), an indicator of diesel exhaust particles, at New York City (NYC) high schools. Outdoor PM 2.5 and BC were monitored continuously for 4-6 weeks at each of 3 NYC schools and 1 suburban school located 20 kilomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 22 publications
(32 reference statements)
2
46
2
1
Order By: Relevance
“…Mean indoor PM 2.5 in this study was higher than levels reported in monitoring studies using optical methods in urban and suburban schools (Branis, Rezácová, and Domasová 2005;Fromme et al 2007;Patel et al 2009;Weichenthal et al 2008) that ranged between 12 and 23 μg/m 3 (min-max range: 1-80 μg/m 3 ). Although guidelines have not yet been developed for the ultra-fine fraction, this size range of PM may entail greater health risks as they penetrate deeper into the lungs and are mainly the products of combustion (Fromme et al 2008).…”
Section: Discussioncontrasting
confidence: 80%
“…Mean indoor PM 2.5 in this study was higher than levels reported in monitoring studies using optical methods in urban and suburban schools (Branis, Rezácová, and Domasová 2005;Fromme et al 2007;Patel et al 2009;Weichenthal et al 2008) that ranged between 12 and 23 μg/m 3 (min-max range: 1-80 μg/m 3 ). Although guidelines have not yet been developed for the ultra-fine fraction, this size range of PM may entail greater health risks as they penetrate deeper into the lungs and are mainly the products of combustion (Fromme et al 2008).…”
Section: Discussioncontrasting
confidence: 80%
“…Exposure to many TRAPs including BC can vary greatly due to changes in traffic patterns and distance from traffic related sources (Dons et al, 2012; Patel et al, 2009). Therefore, personal exposure monitoring, as measured here, is ideal for capturing individual level BC exposure when evaluating relationships between exposures, behaviors and clinical measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies across diverse locations, different indicators of traffic and built environment have been associated with pollutants such as NO 2 , PM 2.5 , and black carbon (Brauer et al, 2008; Morgenstern et al, 2008; Patel et al, 2009b). By examining a diverse set of GIS variables representing traffic proximity, density, vehicle mix, industrial emission sources, and land use characteristics, we aimed to characterize whether particular surrogates of local air pollution mix and perhaps exposures to a mixture of air pollutants were associated with different measures of respiratory health.…”
Section: Discussionmentioning
confidence: 99%